Toxic keratitis after use of wrongly labeled non-ophthalmic medicatio - Mohammad A. Al-Amry; Nada Al-Abdan; Saleh A. AL-Othaimeen (Elsevier, 2017)
We present a 24-year-old female with trauma to her right eye. The patient was prescribed topical Tobramicin-dexamethasone eye drops but the pharmacy dispensed diclofenac diethyl amine ointment. The patient presented to the emergency room with lid edema, conjunctival injection and a corneal epithelial defect and toxic keratitis. The patient was successfully managed with copious irrigation, bandage contact lens and topical antibiotic therapy.